Wild Wales: Its People, Language and Scenery - Borrow, George, 1803-1881 (Salt Lake City, UT : Project Gutenberg, 1996)
"Wild Wales: Its People, Language and Scenery" by George Borrow is a travel book published in 1862. It recounts Borrow's solo walking tour through Wales in 1854, during which he explores the country's landscapes and meets its people. The author takes pride in his self-taught Welsh language skills, which surprise the locals he encounters. His journey spans from North Wales through remote villages and valleys to the industrial South Wales coalfields, offering insights into Welsh social and geographical history. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Wild_Wales
Release date is 1996-09-01
David Price and Jane Gamie
Keywords: Wales -- Description and travel; Borrow, George, 1803-1881 -- Travel -- Wales